Economic opportunities for Mexican women from low socioeconomic status: results from a technical and life skills training program - Shaye S Worthman; Adriana Rueda-Barrios (Revista Iberoamericana de Estudios de Desarrollo)
This study presents the outcomes of a technical and life-skills training program in Mexico aimed to help women from low socioeconomic status (SES) find formal employment in sales, retail, and/or customer service. To determine the extent to which the program reached its target population and its impacts, researchers analyzed a national database of over sixty-eight thousand Mexican beneficiaries from 2016 to 2020 and conducted telephone surveys with a representative sample of women beneficiaries in Veracruz. Results from the national-level analysis of 5,326 women participants identified as low SES indicate that 23 % found better economic and educational opportunities. The state-level analysis of 94 low SES women in Veracruz was higher, with 40 % reporting to have found better opportunities; of those who reported salary information, roughly half improved their income. Lessons learned are discussed regarding reaching target populations and the potential of job training programs in developing countries.